2021
DOI: 10.3171/2020.9.jns202818
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery as the first-line treatment for intracanalicular vestibular schwannomas

Abstract: OBJECTIVEThis report evaluates the outcomes of stereotactic radiosurgery (SRS) as the first-line treatment of intracanalicular vestibular schwannomas (VSs).METHODSBetween 1987 and 2017, the authors identified 209 patients who underwent SRS as the primary intervention for a unilateral intracanalicular VS. The median patient age was 54 years (range 22–85 years); 94 patients were male and 115 were female. Three patients had facial neuropathy at the time of SRS. One hundred fifty-five patients (74%) had serviceabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Comparatively, Ogino et al 13 reported a 5-year serviceable hearing preservation rate of 50.3% among Koos grade IV VS and found a higher chance of preserving serviceable hearing among patients with GR grade I at SRS and those who were younger than 60 years. In another study, Ogino et al 11 investigated intracanalicular VS treated with SRS, and found serviceable hearing preservation rates after SRS of 76.6%, 63.5%, and 27.3% at 3, 5, and 10 years, respectively. The authors also reported age (younger than 55 years) as a statistically significant predictor of serviceable hearing preservation ( P = .011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, Ogino et al 13 reported a 5-year serviceable hearing preservation rate of 50.3% among Koos grade IV VS and found a higher chance of preserving serviceable hearing among patients with GR grade I at SRS and those who were younger than 60 years. In another study, Ogino et al 11 investigated intracanalicular VS treated with SRS, and found serviceable hearing preservation rates after SRS of 76.6%, 63.5%, and 27.3% at 3, 5, and 10 years, respectively. The authors also reported age (younger than 55 years) as a statistically significant predictor of serviceable hearing preservation ( P = .011).…”
Section: Discussionmentioning
confidence: 99%
“…The Gamma Knife planning and treatment protocol were reported previously. 10,11 The median time from VS diagnosis to SRS treatment was 23 months (IQR, 1-51) (Table 1). The median tumor volume was 2.8 cc (IQR, 0.9-5.6), and the VS arose from the right vestibulocochlear nerves in 51.6% of patients.…”
Section: Methodsmentioning
confidence: 99%
“…While chemotherapy has been documented to improve survival in malignant lesions, radiotherapy as a primary or adjuvant modality aims mainly to halt tumor progression. Studies that investigated the efficacy of radiotherapy for meningiomas and schwannomas reported high 10-year PFS rates of up to 90–98% [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. However, since different tumor types respond differently to various modalities, it is essential to tailor a personalized management plan based on the patient tumor pathology and their clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies mentioned that a small subgroup of patients received marginal doses of 8-11 Gy. However, their outcomes were not analyzed separately (23,28,38,79,80). The median marginal dose of our lowdose group was 9 Gy.…”
Section: Discussionmentioning
confidence: 99%